2011
DOI: 10.1111/j.1478-4408.2011.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of the daylight sources for industrial colour control

Abstract: Information is presented based on measurements, published literature and the findings of the CIE Technical Committee TC1‐44 Practical Daylight Sources for Colorimetry. For visual colour control, filtered incandescent lamps, filtered xenon short‐arc lamps, fluorescent lamps and light‐emitting diode sources are used as daylight simulators, while, in today’s industrial reflectance spectrophotometers, pulsed xenon lamps are used. Practical daylight simulators exist with characteristics satisfying the major nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…The reference lamp was a fluorescent lamp supplied by VeriVide Ltd with a high CIE-R a and high metamerism index (MI) category [16]. The latter is another measure of the quality of daylight simulators and its details are given by Hirschler [17] in this special issue of Coloration Technology. The method applies a set of limited metameric pairs, each perfectly matching under a CIE daylight illuminant.…”
Section: Methodsmentioning
confidence: 99%
“…The reference lamp was a fluorescent lamp supplied by VeriVide Ltd with a high CIE-R a and high metamerism index (MI) category [16]. The latter is another measure of the quality of daylight simulators and its details are given by Hirschler [17] in this special issue of Coloration Technology. The method applies a set of limited metameric pairs, each perfectly matching under a CIE daylight illuminant.…”
Section: Methodsmentioning
confidence: 99%
“…Analyzing the concentration of contaminants to the input and output of the Wastewater Treatment Plant (WWTP), it was identified that there is need for improvement of the treatment system in order to maximize the environmental benefits. The dissolved aluminum content increased from itself a viable green alternative targeting its final destination (Hirschler et al, 2011). In this context, application of toxicity tests in order to define the real conditions for the reuse of the generated sludge reveals to be important.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth pointing out that this mixture has a quite variable composition, which, in general, presents high levels of organic matter, nitrogen, phosphorus, micro-nutrients, pathogens and heavy metals prevenient from certain types of dyes (Hirschler et al, 2011). Its application in agriculture, either as a nutrient source for plants or as soil corrective, depending on the sludge's chemical composition, has proven Advanced Oxidation Processes introduction to generate less pollutant effluents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Em diversos segmentos industriais como farmacêutico, papel, cosmético e principalmente o têxtil, ocorre, durante o processo produtivo, a geração de grandes quantidades de águas residuais contendo corantes, surfactantes, íons orgânicos, agentes umectantes, dentre outros. Tais substâncias, alteram os parâmetros físico-químicos das águas superficiais constituindo um real perigo à saúde humana e aos ecossistemas (HIRSCHLER et al, 2011;NIEBISCH et al, 2014;PIRES et al, 2019).…”
Section: Introductionunclassified